Use and Management of Water in A Scarcity Region. The CETYS University Experience in Northwestern Mexico - Azuz-Adeath, Isaac; Romero, María Elena; López, Ulises; Valdes, Adrián; Aguiar, Fernanda (Universitas Diponegoro, 2023)
Abstract. CETYS University is located in the state of Baja California, Mexico. Water scarcity is the main environmental problem in the region. The historic accumulated rain from 1980 to 2021, shows an average of 200 mm/year, with a long-term drought affecting the zone. Considering this fact, CETYS University works to minimize and make more efficient the use of water in all its facilities. Wastewater treatment plants operated in two campuses provide recycled water (8.5 liters per second) for green areas and general use in restrooms facilities. Recycled water is stored in cistern tanks with a total capacity of 82,000 m3, which significantly reduces the need to use external supply of clean city water; also, purification devices give drinking water for students, academics, administrative, and service personnel. Water-efficient appliance usage is a priority in CETYS policies. Considering hand washing taps, toilet flushes, and men's urinals, nearly 88% of the devices are water-efficient. CETYS University complies with the official regulations for preventing pollution from wastewater generated inside campuses. Wastewater goes to the internal treatment plant or the Municipality treatment facilities. Water management at CETYS is a priority to contribute to regional sustainability.Keyword: Water Scarcity, Water Management, Wastewater Treatment, Regional Sustainability